The model of formation of teachers' readiness for science specialties for development of entrepreneurial competence of high school students in postgraduate education - Shorobura, Inna Mykhailivna; Kurysh, Natalia Kostiantynivna (Journal of Education, Health and Sport, 2019)
The success of educational reform is directly dependent on the professional readiness and professional skill of teachers of general secondary education institutions, who are at the epicenter of the New Ukrainian School Concept. That is why the task of institutions of postgraduate pedagogical education is now urgent to search for different approaches and to develop models of forming teachers' readiness, including natural sciences, for the development of key competences of students In the article was analyzed the theoretical and methodological sources on the studied problem, clarifies the essence of such concepts: "entrepreneurial competence", "model", "modeling", "pedagogical model", "cross-cutting learning". The effectiveness of a linear structural model of forming the readiness of science teachers for the development of entrepreneurial competences of high school students in postgraduate education has been developed and substantiated. interrelated tasks between them.